Large deletion mutation of SPAST in a multi‐generation family from Sardinia. (4th November 2013) - Racis, L.; Di Fabio, R.; Tessa, A.; Guillot, F.; Storti, E.; Piccolo, F.; Nesti, C.; Tedde, A.; Pierelli, F.; Agnetti, V.; Santorelli, F. M.; Casali, C.
<x xml:space="preserve">Abstract</x> Background and purpose The hereditary spastic paraplegias (HSP) are characterized by progressive spasticity of the lower limbs, mostly inherited as an autosomal dominant trait. Analyses of large HSP pedigrees could help to better characterize the phenotype due to a single causative mutation. Patients in a seven‐generation kindred carrying a large deletion in SPAST/SPG4 are described. Methods Individuals originating from Sardinia were clinically and genetically studied. Results Sixty‐seven subjects carried a heterozygous deletion encompassing exons 2–17 of SPAST. Fifty patients (53.2 ± 15.4 years) presented a pure form of spastic paraparesis characterized by mild impairment and slow progression. Most patients showed spasticity, increased tendon reflexes in the lower limbs and Babinski sign, whilst weakness was rarely detected and urinary disturbances occasionally reported. Amongst the 17 asymptomatic carriers of the mutation, minimal neurological signs were detected in 11 cases. Conclusions A focus on spasticity, increased tendon reflexes and Babinski sign, more than on weakness, could help clinicians to promote early diagnosis in asymptomatic carriers of SPAST deletions.